Simultaneous monitoring of quantum dots and their assembly and disassembly with PreScission protease using capillary electrophoresis with fluorescence detection. Issue 9 (14th April 2016) - Wang, Jianhao; Li, Jinchen; Wang, Jianpeng; Liu, Li; Li, Jinping; Qin, Haifang; Ding, Shumin; Fu, Minli; Ji, Junling; Jiang, Pengju; Qiu, Lin
Abstract : A novel assay was developed for the simultaneous monitoring of quantum dots and their assembly and disassembly with PreScission protease using capillary electrophoresis with fluorescence detection. Quantum dots and PreScission protease were injected into a capillary sequentially, then mixed and assembled via a thioether bond upon coupling to glutathione S‐transferase tag inside the capillary. The in‐capillary assembly was influenced by the molar ratio and the time interval of injection. Furthermore, the simultaneous monitoring of quantum dots and their assembly with PreScission protease and glutathione induced disassembly was achieved by adjusting the sampling sequence and the time interval of injection. More importantly, the in‐capillary assay could be also applied to the online detection of glutathione.